2002
DOI: 10.1016/s0044-8486(02)00015-7
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Artemia and shellfish to phyllosoma larvae of southern rock lobster (Jasus edwardsii)

Abstract: Newly-hatched phyllosoma larvae from southern rock lobster (Jasus edwardsii) were grown in culture vessels containing 10 l sea water in a flow-through system at 18°C and fed diets of Artemia sp. and shellfish. The survival and growth of larvae to Stage II was higher when fed ongrown (1.5 mm long) Artemia enriched with Isochrysis galbana (Tahitian strain) at 3 ml -1 compared to those fed pieces (0.5-1 mm) of blue mussel (Mytilus edulis planulatus), clam (Katelesia scalarina) or Pacific oyster (Crassostrea gigas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The growth (body lengths and widths) and survival of cultured phyllosomas in this study were similar to those found previously (Tong et al, 1997;Ritar, 2001;Ritar et al, 2002Ritar et al, , 2003. By the end of Stage VI, larval dw had increased 17-fold from hatch.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The growth (body lengths and widths) and survival of cultured phyllosomas in this study were similar to those found previously (Tong et al, 1997;Ritar, 2001;Ritar et al, 2002Ritar et al, , 2003. By the end of Stage VI, larval dw had increased 17-fold from hatch.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, it was likely that the extended starvation was well beyond their point-of-no-return, which for early Stage I phyllosoma was only 4 days (Abrunhosa and Kittaka, 1997). For starved larvae at Stages II, IV and VI, the reserves were insufficient to permit moulting to the next stage, whereas the intermoult interval for these early larval stages is normally just 10-12 days when fed an Artemia diet (Tong et al, 1997;Ritar et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonging the starvation period or even commencing feeding would have resulted in total phyllosoma mortality as this species requires food within the first 4 days post hatching for successful completion of a moult to Stage II (Abrunhosa & Kittaka 1997). A moult to Stage II generally occurs after 9 days of culture (Ritar, Thomas & Beech, in press).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, larval survival between culture tanks is typically variable; mortalities are even low occasionally when pathogen levels remain low (Ritar et al, 2002). In Experiment 1, the bacterial content of the phyllosoma appeared to be a more accurate reflection of their health than the bacterial content of Artemia or culture water.…”
Section: Discussionmentioning
confidence: 91%